Wernicke Encephalopathy after Sleeve Gastrectomy. A Review of the Literature - Angelou Anastasios; Athanasiou Antonios; Diamantis Theodoros; Tsigkris Christos; Alexandrou Andreas (Journal of Digestive Disorders And Diagnosis, 2017)
Objectives: Bariatric surgery has been established as the cornerstone of treatment of morbid obesity with good immediate and long-term results. Nutrient deficiencies though, can be an important long-term complication and may lead to hematological, metabolic and especially neurological disorders which are not always reversible. Thiamine (vitamin B1) deficiency has been reported both after restrictive and malabsorptive procedures. The aim of this study is to review all cases that presented with Wernicke Encephalopathy after sleeve gastrectomy. Methods: A review of the literature was conducted to evaluate all sleeve gastrectomies performed till today and caused Wernicke encephalopathy to the patients. Demographic data, operative parameters, postoperative outcomes were collected and assessed. Results: A total of 13 studies, including 13 patients were analyzed. Patients ranged in age from 17 to 55 years. The onset of Wernicke encephalopathy occurred as early as 3 weeks after surgery to as late as 60 weeks after surgery. When symptoms of Wernicke encephalopathy developed, patients had lost from 19 kg up to 60 kg of body weight. Conclusions: Micronutrient deficiencies and particularly B1 deficiency can occur after LSG, although rarely. Preoperative nutritional assessment and postoperative follow-up plan, should signs of Wernicke’s encephalopathy be traced, is recommended in all patients.
Keywords: bariatric surgery